Introducing nuclear power in Turkey: A historic state strategy and future prospects - Jewell, Jessica; Ateş, Seyithan Ahmet (Elsevier Science, 2015)
Turkey is currently in the middle of its sixth attempt over the last 60 years to introduce nuclear power. This paper analyzes Turkey's past and present motivation, capacity and strategies to identify the factors which influence deployment of nuclear power and draw lessons for other nuclear newcomer countries. While existing literature points to a correlation between nuclear power, strong state involvement, centralized energy planning and the rhetoric linking energy to national prestige and security, we show that these factors are not sufficient for a successful nuclear program. We also show that autocratic rule and nuclear weapons aspirations can undermine rather than support the development of civilian nuclear power as it is often presumed in the literature. Turkey's current strategy based on intergovernmental agreements with Russia and Japan is laced with irony since it is motivated by energy security considerations and yet relies on foreign entities for construction, ownership and operation of nuclear power plants as well as the development of human capacity. Although Ankara intends to build the third nuclear power plant with own resources this seems unlikely based on the South Korean and Japanese experience, both of which needed much more time and effort to localize the industry.
WOS: 000218708600026
Keywords: Nuclear Power; Nuclear Energy; Energy Security; Turkey